Grass Cutter Robot with Bluetooth Module - Bhuvaneswari Balachander, Y. Hemanth (International Journal of Advanced Science and Technology, 2020)
In subsisting system the motored powered engines are utilized for the grass cutting. The fundamental downside of the subsisting framework is the different individual is required to Operate the machine. In any case, in our framework we actualize the BLUETOOTH module just as the ULTRASONIC sensor. Right now module is utilized to control the entire gadget. Ultrasonic sensor is utilized to distinguish the impediment and send the message through the LCD show. A sun powered board will be connected on the highest point of the robot due to this decreases the force issue. The framework is utilized for the House gardens, little ranches, nurseries, play areas and so forth.